Pedagogy, Andragogy, And Heutagogy: Differences And Relevance For 21st Century Teachers: Pedagogi, Andragogi, Dan Heutagogi: Perbedaan Dan Relevansinya Bagi Guru Abad Ke-21 - Mutmainnah; Cahyani, Okik Dwi; Afriani, Linda (Transformation of Islamic Management and Education, 2024)
This study was conducted with the aim of determining the differences in pedagogical, andragogical, and heutagogical learning theories. Heutagogical theory is a continuum of pedagogy and andragogy. Based on the understanding of the PAH continuum (Pedagogy-Andragogy-Heutagogy), we want to determine the relevance of the PAH learning theory to the characteristics of teachers in the 21st century. The research method used is a literature review with the aim of determining the concepts of various literatures related to the PAH continuum and the suitability or not of the learning theory with 21st century teachers. The results of this study indicate that pedagogical theory focuses on the teacher-centered learning process and is not centered on students. Andragogical theory is a learning process that emphasizes that to become active learners, they need to independently plan their learning needs and know how they obtain and feel satisfied. Heutagogical theory emphasizes that students have full autonomy in the learning process in the classroom by creating an active and enjoyable learning atmosphere for them. Learning in the 21st century demands innovation so that education should not impose limitations on learners to be able to expand their knowledge, so that for teachers the theory of andragogy is still considered relevant for 21st century learning, while heutagogy is more suitable for learning in higher education.